Pengetahuan tentang Kesehatan Mental Lansia - Tanggung Jawab Siapa? - Husna, Faidatul (Maliki Interdisciplinary Journal, 2024)
Elderly is a phase of life that every level of human being will definitely go through. As people get older, the life challenges that humans will go through will also increase, including the elderly. Therefore, this research focuses on studying those who have the biggest role in being responsible for knowledge about the elderly. Researchers conducted a literature review of previous journals and articles that have the greatest continuing role in research, have knowledge related to the elderly, and have the greatest responsibility for the elderly. The research results show that there are three biggest roles, namely oneself, relatives and the role of social society.